A Review of the Pedunculopontine Nucleus in Parkinson's Disease - French, Isobel T.; Muthusamy, Kalai A. (Frontiers in Aging Neuroscience, 2018)
The PPN is a cluster of neurons situated in the upper pons and is columnar in shape. It is located in the upper brainstem and forms part of the mesenphalic locomotor region, or MLR. It contains cholinergic and non-cholinergic neurons, and has afferent and efferent connections to the cerebral cortex, thalamus, BG, cerebellum and spinal cord. The PPN is known to play an imperative role in movement, motivation, and cognitive facets of composite behavioral responses. Understanding the physiology and functionality of the PPN together with its relationships with the BG and other neuronal circuitries would indefinitely help in producing better treatment interventions. This would be exceptionally important since the PPN is implicated in a number of neurodegenerative diseases, particularly in Parkinson’s disease.